2019
DOI: 10.1097/spv.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Cohort Study on the Perioperative Risk Factors for Transient Voiding Dysfunction After Apical Prolapse Repair

Abstract: Objectives The primary aim was to compare the incidence of transient voiding dysfunction (TVD) between vaginal uterosacral ligament suspension, sacrospinous ligament fixation, and robotic sacrocolpopexy. Secondarily, we identified risk factors for TVD and associated postoperative complications. Methods This was a retrospective cohort study of women who underwent apical repair at 1 institution. Data were collected from electronic medical records and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Overall, only 23% of our cohort failed their first active voiding trial compared to 70% of women undergoing multi-compartment vaginal native tissue repair at our institution prior to ERAS implementation (3). Similarly, in a retrospective study of 360 patients who underwent apical repair via uterosacral ligament suspension, sacrospinous ligament fixation or robotic sacrocolpopexy, the overall failure rate was 39% (2). ERAS protocols typically advocate for the incorporation of standing doses of anti-inflammatory medication and acetaminophen without utilization of narcotics, a regimen that improves pain without interfering with return of bladder function.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Overall, only 23% of our cohort failed their first active voiding trial compared to 70% of women undergoing multi-compartment vaginal native tissue repair at our institution prior to ERAS implementation (3). Similarly, in a retrospective study of 360 patients who underwent apical repair via uterosacral ligament suspension, sacrospinous ligament fixation or robotic sacrocolpopexy, the overall failure rate was 39% (2). ERAS protocols typically advocate for the incorporation of standing doses of anti-inflammatory medication and acetaminophen without utilization of narcotics, a regimen that improves pain without interfering with return of bladder function.…”
Section: Discussionmentioning
confidence: 91%
“…Rates of postoperative incomplete bladder emptying after pelvic reconstructive surgery have a wide reported variance that ranges from 13% [1] to 39% [2]. Factors affecting postoperative urinary retention (POUR) include the timing of the voiding trial [3], method of prolapse repair [4], concomitant hysterectomy, larger cystoceles, severe intra-operative blood loss, levator plication, and Kelly plication [5].…”
Section: Introductionmentioning
confidence: 99%
“…Transient urinary retention requiring temporary catheterization occurs commonly after both reconstructive and obliterative pelvic organ prolapse surgery 1–5 . Many studies have identified possible risk factors for the development of postoperative urinary retention after prolapse repairs; however, the optimal strategy for catheter management postoperatively is unclear 1–3,6 .…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Many studies have identified possible risk factors for the development of postoperative urinary retention after prolapse repairs; however, the optimal strategy for catheter management postoperatively is unclear. [1][2][3]6 Options for managing postoperative transient urinary retention include indwelling transurethral catheter (TUC), clean intermittent catheterization (CIC), and planned suprapubic catheter (SPC) placement at the time of prolapse repair. Each option has unique advantages and disadvantages to include urinary tract infection (UTI) risk, ease of patient use, and patient comfort.…”
mentioning
confidence: 99%
See 1 more Smart Citation